Penerapan Pembelajaran Vokasional Tata Rias pada Anak Tunarungu Kelas X SMALB di SLB Negeri Pembina Kota Kupang - Luluporo, Chelsy Wandira; Wangge, Vinsensius; Selan, Ot Bil Wilson; Liunokas, Oded; Ajito, Timoteus (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to improve the ability of students with mild hearing impairment in Grade X SMALB at SLB Negeri Pembina Kota Kupang to recognise facial makeup tools and materials. Students with mild hearing impairment have hearing difficulties that affect their ability to speak, understand instructions, and communicate verbally, thus requiring a more concrete and practical learning approach. The research was conducted using the Classroom Action Research method with a descriptive qualitative approach, with data collection through observation, interviews, documentation, and makeup practice tests. The learning was designed based on vocational practices combined with video tutorial media and was carried out in two cycles, each consisting of two meetings. The results showed a significant improvement from the pre-test to the post-test in cycle II, where the average FA score rose from 41 to 94, KA from 45 to 85, and EM from 90 to 98. In addition to the increase in scores, students also showed improvement in independence, confidence, and basic makeup skills, indicating that the learning model applied was effective in supporting the learning needs of students with mild hearing impairment.